Pengembangan Digital Marketing Pada UMKM Warkop Harapan Jaya Berbasis Website di Kota Padang - Ilham Saputra; Wela Purnamasari; Silfia Nabila Ramadani; Sularno; Novadilastri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2024)
This research examines the development of digital marketing for UMKM Warkop Harapan Jaya in Padang, West Sumatra. The goal is to design an effective blog to support business marketing and digitalization strategies. Using descriptive qualitative methods, data was collected through observations and interviews in September 2024. The results show that Warkop Harapan Jaya has not optimized digital potential. As a solution, a blog was designed and implemented to expand marketing reach and increase customer interaction. In conclusion, the development of this blog is expected to increase online visibility and business growth, while providing insight into the importance of digital technology adoption for MSMEs.